2015
DOI: 10.1128/aac.00267-15
|View full text |Cite
|
Sign up to set email alerts
|

Lumefantrine and Desbutyl-Lumefantrine Population Pharmacokinetic-Pharmacodynamic Relationships in Pregnant Women with Uncomplicated Plasmodium falciparum Malaria on the Thailand-Myanmar Border

Abstract: Artemether-lumefantrine is the most widely used antimalarial artemisinin-based combination treatment. Recent studies have suggested that day 7 plasma concentrations of the potent metabolite desbutyl-lumefantrine correlate better with treatment outcomes than those of lumefantrine. Low cure rates have been reported in pregnant women with uncomplicated falciparum malaria treated with artemether-lumefantrine in northwest Thailand. A simultaneous pharmacokinetic drug-metabolite model was developed based on dense ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 33 publications
4
33
0
Order By: Relevance
“…While resistance to artemisinin has emerged in South-East Asia [8] and a degree of resistance to the partner drugs exists in some parts of the world, both treatments remain highly effective in most African malariaendemic areas [9][10][11][12]. The pharmacokinetic properties of each drug are relatively well characterized: lumefantrine and its metabolite desbutyl-lumefantrine have terminal elimination half-lives of 1-10 days [1,[13][14][15][16], while desethylamodiaquine, the active metabolite of amodiaquine, has a half-life of 4-10 days [1,[17][18][19][20][21][22]. However, these estimates do not provide information on the duration of post-treatment prophylaxis which also depends on the pharmacodynamics of the drug.…”
Section: Introductionmentioning
confidence: 99%
“…While resistance to artemisinin has emerged in South-East Asia [8] and a degree of resistance to the partner drugs exists in some parts of the world, both treatments remain highly effective in most African malariaendemic areas [9][10][11][12]. The pharmacokinetic properties of each drug are relatively well characterized: lumefantrine and its metabolite desbutyl-lumefantrine have terminal elimination half-lives of 1-10 days [1,[13][14][15][16], while desethylamodiaquine, the active metabolite of amodiaquine, has a half-life of 4-10 days [1,[17][18][19][20][21][22]. However, these estimates do not provide information on the duration of post-treatment prophylaxis which also depends on the pharmacodynamics of the drug.…”
Section: Introductionmentioning
confidence: 99%
“…Artemether-lumefantrine is a highly efficacious artemisinin-based combination therapy approved by WHO for use in the 2nd and 3rd trimesters of pregnancy. Previous studies have shown that the standard 3-day treatment in later pregnancy is associated with lower plasma concentrations of artemether, dihydroartemisinin (DHA), and lumefantrine and more rapid elimination of lumefantrine (5)(6)(7). Low lumefantrine plasma concentrations are associated with therapeutic failure in the treatment of falciparum malaria (8)(9)(10).…”
mentioning
confidence: 99%
“…This may underpin the unsatisfactory low cure rates of artemether‐lumefantrine in this vulnerable group. A simultaneous population‐based PK drug‐metabolite modeling indicates suboptimal of artemether‐lumefantrine for P falciparum in this area, and increased treatment duration is proposed 168 . The study in Uganda, however, demonstrates comparable overall PK exposures to artemether, dihydroartemisinin, and lumefantrine during pregnancy, indicating no requirement of dose adjustment 169 .…”
Section: Antimalarial Dose Optimization In Vulnerable Groupsmentioning
confidence: 93%